2007
DOI: 10.1016/s1015-9584(09)60134-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anuric Renal Failure Following Jering Bean Ingestion

Abstract: Djenkol beans or jering (Pithecellobium jeringa) is a traditional delicacy consumed by the local population in Malaysia. Jering poisoning or djenkolism is characterized by spasmodic pain, urinary obstruction and acute renal failure. The underlying pathology is an obstructive nephropathy, which is usually responsive to aggressive hydration and diuretic therapy. We present a case of djenkolism following ingestion of jering. The patient required urgent bilateral ureteric stenting following the failure of conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…As illustrated in Figure 1, we only found five publications which matched our inclusion criteria in our electronic search initially, and all of them were case reports [29][30][31][32][33] . Furthermore, we have gathered other five publications through the reviews [34][35][36][37][38] and another case report 39 has been manually selected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Figure 1, we only found five publications which matched our inclusion criteria in our electronic search initially, and all of them were case reports [29][30][31][32][33] . Furthermore, we have gathered other five publications through the reviews [34][35][36][37][38] and another case report 39 has been manually selected.…”
Section: Resultsmentioning
confidence: 99%
“…The serum creatinine levels raised from 1.33 mg/dL to 9.5 mg/dL in a period of four days, when a bilateral ureteric stenting showed to be decisive in his treatment. Further clinical investigation revealed that the patient had been taking jering bean, which had been previously implicated in renal diseases 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation of flank pain, nausea, vomiting, and gross hematuria is most compatible with ureteral and urethral obstruction by djenkolic acid crystals. Crystals may lacerate renal tissue and cause bleeding, or – in some cases – obstruction with sludge necessitates passage of a urethral catheter or stent 13,17…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of severe djenkolism with anuria do not respond to conservative therapy and require surgical intervention. There are case reports of the irrigation of the urethra, placement of urinary catheters, as well as stents to bypass or to resolve urinary obstruction caused by djenkolic acid, sludge, and calculi 13,17…”
Section: Discussionmentioning
confidence: 99%